Changes of Hemodynamic Parameters at the Preparatory Stage of Periodization Training among the Male and Female Athletes Involved in Different Running Events (Indian Journal of Public Health Research & Development, 2021)
The present study was conducted to determine the changes occurs in hemodynamic variables of (HR, LVSD,LVESD, Stroke volume, Cardiac output) at different training phases of periodization in athletic events suchas, middle distance and long-distance running between the male and female novice athletes in athletictraining center at maychew, Ethiopia.Materials and Method: In this qazi-experimental study, 18 athletes selected from different phases of trainingat maychew athletic training center in Ethiopia. The novice athletes of male and female were selected by theirperformance in the regional wise, as they are novice athletes in the training center they used to go for morethan a year training however the researcher wanted to know the hemodynamic parameters changes occursbefore the athletes used to engage in specific period of training. To analyze the hemodynamic parameterthe subjects were taken to the comprehensive specialized regional hospital then, "Echocardiography  was performed by VIVID E-19(General Electric) undertaken using a 2.5MHz probe "are used to calculate several hemodynamic parameters the values of hemodynamic parameters were recorded at intervals. The recorded data were analyzed by SPSS 21 software, using independent t-test, it is concluded that while comparing the male and female novice athletes male athletes are dominating in longdistance then female athletes are dominating in middle distance running events.
Keywords: Hemodynamic, athletes, events, echocardiograph.